7 Sentinel lymph node biopsy versus lymphadenectomy for intermediate and high grade endometrial cancer staging (SENTOR trial): a prospective multicenter cohort study. (13th November 2020) - Cusimano, M; Vicus, D; Pulman, K; Bernardini, MQ; Bouchard-Fortier, G; Laframboise, S; May, T; Hogen, L; Covens, A; Gien, LT; Kupets, R; Rouzbahman, M; et al.
Abstract : Background: It is unclear whether sentinel lymph node biopsy (SLNB) can replace lymphadenectomy in women with high grade endometrial cancer (EC). We performed a prospective multicenter cohort study (the SENTOR trial) to evaluate the diagnostic accuracy of SLNB using indocyanine green in intermediate and high grade EC (NCT01886066 ). Methods: Patients with clinical stage I grade 2 endometrioid or high grade EC scheduled for minimally invasive hysterectomy at three academic centers in Toronto, Canada, were prospectively enrolled for SLNB followed by pelvic (PLND) and para-aortic lymphadenectomy (PALND) as the reference standard. The study was powered to determine sensitivity of the SLNB algorithm as the primary endpoint. Results: We enrolled 156 patients (126 high grade); all underwent SLNB and PLND, and 106 (84%) with high grade EC underwent PALND. Sentinel lymph node detection rates were 97% per patient (95% CI 94–99), 88% per hemipelvis (95% CI 83–91), and 78% bilaterally (95% CI 70–84). Of 27 patients (17%) with nodal metastases, 26 were correctly identified by the SLNB algorithm, yielding a sensitivity of 96% (95% CI 81–100), false negative rate of 4% (95% CI 0–19), and negative predictive value of 99% (95% CI 96–100). Only one patient (0.6%) was misclassified by the SLNB algorithm. Two of 27 node-positive patients (7.5%) were identified outside traditional PLND boundaries, and five of 27 (18.5%) required immunohistochemistry for diagnosis. Conclusion: SLNB has comparable, if not superior, diagnostic accuracy relative to lymphadenectomy in high grade EC patients. SLNB is a viable option for the surgical staging of EC.